Speech Dialogue System-Based Environmental Resource Allocation and Online English Teaching and IoT Applications. (22nd September 2022) - Wang, Kunfeng
Abstract : For the online teaching of English and the allocation of environmental resources, the conventional methods are difficult to adapt to the increased load in time when the business volume increases, and their practicability has obvious shortcomings. Aiming at this problem, this paper puts forward the environmental resource allocation and online English teaching based on the voice dialogue system. Based on the English teaching content, the vocabulary information table and dialogue information table which are input into the voice dialogue system are designed. In the user's usage, the dialogue sent by the user is matched with, and each group of matching results is taking as the target. Environmental resources are allocated for each group of matching results with the help of the dispatcher in the voice dialogue system, and the optimal allocations of single goal and multiple goals are realized. On this basis, the online teaching architecture is designed, and the above contents are deployed to the teaching architecture. It supports the multichannel interaction between users and the online English teaching platform and realizes independent online English learning. The experimental results show that the teaching method based on the voice dialogue system has stable environmental resource allocation, low blocking rate, and high teaching quality score, and the overall practicability has been significantly improved.